Rural Transport Survey in Ethiopia - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset was generated to assess the impact of market access on different socioeconomic indicators. The study focuses on Alefa woreda in the rugged terrain of northwestern Ethiopia just west of Lake Tana and approximately 100 kilometers from the city of Gonder. This is an isolated area with little to no electricity and mobile phone access and without any development or humanitarian assistance programs provided by non-governmental organizations. The sample area was chosen because the large variation in transportation costs over relatively short distances in the woreda allows to carefully assess the impact of these varying costs by comparing it with a situation of similar physical and climatic conditions. The survey took place shortly after the main cropping season (meher) harvest over a five-week period in November and December 2011, interviewing 850 households. The data collected includes household demographics, land and agricultural production, housing quality and household assets, input access, expenditures and consumption, and anthropometrics of mother and children among others.